SOD1 Is an Integral Yet Insufficient Oxidizer of Hydrogen Sulfide in Trisomy 21 B Lymphocytes and Can Be Augmented by a Pleiotropic Carbon Nanozyme - Karthik Mouli; Anton V. Liopo; Larry J. Suva; Kenneth R. Olson; Emily A. McHugh; James M. Tour; Paul J. Derry; Thomas A. Kent (MDPI AG, 2024)
Down syndrome (DS) is a multisystemic disorder that includes accelerated aging caused by trisomy 21. In particular, overexpression of cystathionine-β-synthase (CBS) is linked to excess intracellular hydrogen sulfide (H2S), a mitochondrial toxin at higher concentrations, which impairs cellular viability. Concurrent overexpression of superoxide dismutase 1 (SOD1) may increase oxidative stress by generating excess hydrogen peroxide (H2O2) while also mitigating the toxic H2S burden via a non-canonical sulfide-oxidizing mechanism. We investigated the phenotypic variability in basal H2S levels in relation to DS B lymphocyte cell health and SOD1 in H2S detoxification. The H2S levels were negatively correlated with the DS B lymphocyte growth rates but not with CBS protein. Pharmacological inhibition of SOD1 using LCS-1 significantly increased the H2S levels to a greater extent in DS cells while also decreasing the polysulfide products of H2S oxidation. However, DS cells exhibited elevated H2O2 and lipid peroxidation, representing potential toxic consequences of SOD1 overexpression. Treatment of DS cells with a pleiotropic carbon nanozyme (pleozymes) decreased the total oxidative stress and reduced the levels of the H2S-generating enzymes CBS and 3-mercaptopyruvate sulfurtransferase (MPST). Our results indicate that pleozymes may bridge the protective and deleterious effects of DS SOD1 overexpression on H2S metabolism and oxidative stress, respectively, with cytoprotective benefits.